Phraseodidactics in teaching Croatian as L2 - Korljan Bešlić, Josipa (ZFD 10: Zbornik radova s Međunarodnoga znanstvenog skupa Zadarski filološki dani 10 održanog u Zadru 10. studenoga 2023., 2026)
Phraseodidactics is a part of applied phraseology and is an essential component of teaching and mastering a foreign language. It is a relatively young discipline that is often overlooked in education. In the introductory part of this paper, we will present previous research and methodology based on cognitive linguistics. The central part of the paper emphasizes the importance of integrating phraseology into the teaching of Croatian as an L2, especially at higher levels. A complete understanding of the phraseology of a specific language implies proficiency in that language, and intercultural competence is extremely important in this context. Examples of the best practices in teaching other languages as foreign languages, as well as in teaching Croatian as an L2, will be provided. The paper provides an overview of the possibilities of applying phraseodidactics, including contrastive phraseology, and also examines the utility of artificial intelligence (ChatGPT) in phraseological teaching in line with the development of new technologies. It leaves open the question of possibilities for improving phraseological teaching of Croatian as an L2.